Intraocular fluid analysis-guided precision therapy in the treatment of acute retinal necrosis syndrome - Xiao Yu; Ziqing mao; Yuling Zou; Yao Zhao; Huimin Fan; Teng Liu; Yiming Lei; Hua Zou; Zhipeng You (Scientific Reports)
Abstract Investigate intraocular fluid testing’s role in ARNs management and prognosis. 46 ARNs patients (49 eyes) treated from 2021 to 2023 were divided into precision (n = 22) and conventional (n = 24) groups based on intraocular fluid testing. Precision group received intravitreal ganciclovir (20 mg/ml [viral copies < 5 × 106] or 40 mg/ml [> 5 × 106]) twice weekly; conventional group received fixed 20 mg/ml. BCVA, viral copies, cytokines (IL-6, IL-8, IL-10), and biomarkers (VCAM, VEGF, BFGF) were analyzed. No baseline differences in BCVA, IOP, or clinical features between groups (P > 0.05). Precision group showed fewer injections, higher final BCVA, and lower retinal detachment rates (P < 0.05). Viral copies negatively correlated with final BCVA (P < 0.05). In precision group: viral copies positively correlated with injection frequency, IL-6, IL-8, VCAM, BFGF; retinal necrosis extent positively linked to initial/final BCVA but inversely with IL-6, IL-8, and viral load. Conventional group showed retinal necrosis involvement positively correlated with detachment risk (P < 0.05). Intraocular fluid testing optimizes ARNs treatment personalization, improves outcomes, and enhances prognostic evaluation.